Long-chain branched polypropylene microporous foam material based on rare-earth self-assembly beta nucleating agent and preparation method of long-chain branched polypropylene microporous foam material

By using rare earth self-assembled beta nucleating agent and supercritical CO2 foaming process in long branched polypropylene, a stable three-dimensional physical crosslinking network structure is formed, which solves the problem of uneven dispersion of traditional beta nucleating agents in LCBPP matrix, and significantly improves the thermal stability and mechanical properties of the material.

CN119639067APending Publication Date: 2025-03-18BEIJING TECH & BUSINESS UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411699672.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Traditional beta nucleating agents are unevenly dispersed in long branched polypropylene (LCBPP) matrix, making it difficult to form a stable physical crosslinking structure, resulting in limited effects of the material in crystallization, cell control and mechanical enhancement.

Method used

Rare earth self-assembled β nucleating agent is blended with long branched polypropylene, and through molding and supercritical CO2 foaming processes, a stable three-dimensional physical crosslinking network structure is formed to improve cell density and mechanical properties.

Benefits of technology

It significantly improves the thermal stability, toughness and mechanical strength of long-branched polypropylene foam materials, improves the uniformity and density of bubble cells, and is suitable for automobiles, construction, aerospace and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119639067A_ABST
    Figure CN119639067A_ABST
Patent Text Reader

Abstract

The invention provides a long-chain branch polypropylene microporous foam material based on a rare earth self-assembly beta nucleating agent and a preparation method thereof. The preparation method comprises the following steps: 1, blending long-chain branched polypropylene and a rare earth self-assembly beta nucleating agent to obtain a blend; 2, carrying out compression molding on the blend to obtain a to-be-foamed sample; and step 3, carrying out foaming treatment on the to-be-foamed sample through a foaming agent to obtain the long-chain branch polypropylene microporous foam material, wherein the addition amount of the rare earth self-assembly beta nucleating agent is 2 to 5 phr based on 100 phr of long-chain branched polypropylene. The foam material is high in melt strength, cell growth is inhibited, cell density is enhanced, thermal stability and toughness of the long-chain branch polypropylene foam material are improved, and the obtained foam material keeps excellent mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a long-chain branched polypropylene microporous foam material based on a rare earth self-assembly beta nucleating agent and a preparation method thereof, belonging to the technical field of polymer material processing. Background Art

[0002] Polypropylene (PP) foam materials have been widely used in the fields of construction, automobiles, packaging, consumer goods, etc. due to their low density, excellent heat resistance, good processing performance and economy. However, there is still room for improvement in mechanical strength, cell uniformity, thermal stability, etc. of PP foam materials, especially under low density conditions. β-crystalline polypropylene (β-PP) has become an important research direction for polypropylene foam modification because it has better toughness and thermal deformation stability than traditional α-crystalline polypropylene. Studies have shown that the introduction of β-nucleating agents can effectively increase the crystallinity of β-crystals in the PP matrix, thereby improving the comprehensive performance of the material.

[0003] However, the dispersion of traditional β-nucleating agents (such as inorganic, condensed ring compounds, amide compounds, dicarboxylates, polymers, etc.) in the long-chain branched polypropylene (LCBPP) matrix is ​​uneven, and it is difficult to form a stable physical cross-linked structure, resulting in limited effects in crystallization, pore control and mechanical enhancement. In addition, the role of conventional nucleating agents is mainly limited to crystallization induction, and the control ability of microporous foam structure is insufficient, especially in terms of pore size, density and distribution uniformity, which still has room for improvement.

[0004] Based on this, it is of great significance to propose an innovative method to construct high-performance LCBPP foam materials with high content of β-crystalline phase and dense pore structure. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a long-chain branched polypropylene microporous foam material based on a rare earth self-assembly β-nucleating agent and a preparation method thereof. The foam material of the present invention has high melt strength, improves the thermal stability and toughness of the long-chain branched polypropylene foam material, and can maintain excellent mechanical strength.

[0006] To achieve the above object, in a first aspect, the present invention provides a method for preparing a long-chain branched polypropylene microporous foam material based on a rare earth self-assembly β-nucleating agent, which comprises the following steps:

[0007] Step 1: blending long-chain branched polypropylene with a rare earth self-assembly β-nucleating agent to obtain a blend;

[0008] Step 2: Compression molding the blend to obtain a sample to be foamed;

[0009] Step 3: The sample to be foamed is foamed by a foaming agent to obtain the long-chain branched polypropylene microporous foam material;

[0010] Wherein, based on 100phr long-chain branched polypropylene as the benchmark, the addition amount of the rare earth self-assembly β-nucleating agent is 2-5phr. If it is higher than this range, agglomeration may occur, resulting in a sharp decrease in the mechanical properties of the long-chain branched polypropylene matrix; in addition, if the addition amount of the nucleating agent is too much, the nucleation effect is not good during the foaming process, and uneven cell distribution and cell merging are likely to occur, resulting in a decrease in the mechanical properties of the foam.

[0011] According to a specific embodiment of the present invention, preferably, based on 100 phr of long-chain branched polypropylene, the added amount of the rare earth self-assembly β-nucleating agent is 2-4 phr.

[0012] According to a specific embodiment of the present invention, preferably, the long-chain branched polypropylene is selected from one or a combination of two or more of HMS-WB140, E02ES, and T30S, and more preferably HMS-WB140. Specifically, HMS-WB140 is produced by Borealis; Sinopec and Beijing Research Institute of Chemical Industry have jointly developed E02ES high melt strength polypropylene, and T30S is a linear isotactic polypropylene. Among them, HMS-WB140 has high melt strength, good foaming performance, the widest application, and the best effect.

[0013] According to a specific embodiment of the present invention, preferably, the rare earth self-assembling β nucleating agent is selected from WBG-II. The manufacturer of WBG-II is Guangdong Weilinna Company. The WBG-II of the present invention can melt and self-assemble at about 280-290°C, while other types of nucleating agents (such as aromatic dicarbonamides and aromatic amides) cannot be completely melted at this temperature, and there is no self-assembly or the self-assembly is incomplete. The structural uniqueness of the rare earth self-assembling β nucleating agent can greatly improve the mechanical properties and pore uniformity of LCBPP.

[0014] According to a specific embodiment of the present invention, preferably, the step 1 further comprises: after blending the long-chain branched polypropylene and the rare earth self-assembly β nucleating agent, adding an antioxidant to obtain a blend; wherein, based on 100phr of the long-chain branched polypropylene, the amount of the antioxidant added is 0-5phr, more preferably 0.5-2phr. Specifically, the blend is added to a torque rheometer, melt blended to make it uniformly mixed, and an antioxidant is added to avoid oxidative degradation during the blending process.

[0015] According to a specific embodiment of the present invention, preferably, the antioxidant is selected from antioxidant 1010 and / or antioxidant 168, more preferably antioxidant 1010. Wherein, antioxidant 1010 is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and antioxidant 168 is tris[2,4-di-tert-butylphenyl]phosphite.

[0016] According to a specific embodiment of the present invention, preferably, the blending temperature is 150-200°C, more preferably 170-190°C; if the temperature is too low, the long-chain branched polypropylene does not melt, resulting in uneven mixing, while if the temperature is too high, the long-chain branched polypropylene is easily oxidized and degraded.

[0017] According to a specific embodiment of the present invention, preferably, in step 1, the blending speed is 50-100 rpm; more preferably 60-90 rpm.

[0018] According to a specific embodiment of the present invention, preferably, in step 1, the blending time is 6-12 minutes, more preferably 8-12 minutes.

[0019] According to a specific embodiment of the present invention, preferably, in step 2, the blend is processed into a predetermined shape by a molding device, so that the rare earth self-assembled β nucleating agent is fully melted, and then spontaneously forms a dendritic three-dimensional physical cross-linked network structure, and improves the melt strength to obtain a pre-foaming sample.

[0020] According to a specific embodiment of the present invention, preferably, in step 2, the temperature of the compression molding is 250-300°C, more preferably 280-300°C, and further preferably 280-290°C.

[0021] According to a specific embodiment of the present invention, preferably, in step 2, the compression molding time is 2-5 minutes.

[0022] According to a specific embodiment of the present invention, preferably, in step 2, the blend is compression molded to obtain a long-chain branched polypropylene matrix material, that is, a sample to be foamed; preferably, the β-crystal crystallinity of the sample to be foamed is 1%-10%.

[0023] According to a specific embodiment of the present invention, preferably, in step 3, the sample to be foamed is subjected to a foaming treatment by supercritical CO2 and then maintained under pressure to obtain the long-chain branched polypropylene microporous foam material. Specifically, the sample to be foamed is placed in an autoclave and filled with CO2 gas. After soaking, the pressure is quickly released to normal pressure to obtain the long-chain branched polypropylene microporous foam material.

[0024] The present invention adopts a supercritical CO2 foaming process, so that the rare earth self-assembly β nucleating agent used can spontaneously form a stable fibrous and dendritic structure at a specific temperature, become a physical cross-linking point in the melt, and inhibit pore expansion and refine pore size during the foaming process.

[0025] According to a specific embodiment of the present invention, preferably, in step three, the pressure of the foaming treatment is 5-17 MPa, more preferably 8-15 MPa.

[0026] According to a specific embodiment of the present invention, preferably, in step three, the temperature of the foaming treatment is 140-170°C, more preferably 140-150°C.

[0027] According to a specific embodiment of the present invention, preferably, in step three, the pressure holding time is 0.1-5h, more preferably 1-2h.

[0028] In a second aspect, the present invention provides a long-chain branched polypropylene microporous foam material prepared by the above-mentioned method for preparing a long-chain branched polypropylene microporous foam material.

[0029] According to a specific embodiment of the present invention, preferably, the average diameter of the pores of the long-chain branched polypropylene microporous foam material is 5-13 μm.

[0030] According to a specific embodiment of the present invention, preferably, the cell density of the long-chain branched polypropylene microporous foam material is 2×10 8 -6×10 9 Pieces / cm 3 , based on the volume of the long-chain branched polypropylene microporous foam material; more preferably 3.5×10 9 -6×10 9 Pieces / cm 3 .

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The invention prepares the foam material by using a supercritical CO2 foaming process in a long-chain branched polypropylene matrix through the use of a rare earth self-assembly beta nucleating agent, thereby increasing the melt strength and pore density of the material, and further improving the thermal stability and toughness of the long-chain branched polypropylene foam material.

[0033] The present invention can also promote the rare earth self-assembling β-nucleating agent to spontaneously form a stable three-dimensional physical cross-linked network structure in the long-chain branched polypropylene matrix by adjusting the content of the rare earth self-assembling β-nucleating agent, the blending temperature, the molding temperature, etc., providing abundant pore nucleation sites, so that the obtained foam material maintains excellent mechanical strength under high temperature and high load conditions and reduces the pore size.

[0034] The long-chain branched polypropylene microporous foam material prepared by the invention has excellent crystallization performance and dense pore structure, and has broad application prospects in the fields of automobiles, construction, aerospace, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a diagram of the formation mechanism and foaming mechanism of rare earth self-assembled β nucleating agents.

[0036] Figure 2 This is a rheological test graph of the effect of rare earth self-assembled β-nucleating agent on the storage modulus of LCBPP melt.

[0037] Figure 3 These are the DSC and XRD diagrams of foam materials with different contents of rare earth self-assembly β-nucleating agents.

[0038] Figure 4 These are the tensile strength and impact strength test graphs of foam materials with different contents of rare earth self-assembly β-nucleating agents.

[0039] Figure 5 These are polarizing microscope and scanning electron microscope images when the rare earth self-assembly β nucleating agent is 2.5 phr.

[0040] Figure 6 This is a diagram of the pore structure of foam materials with different contents of rare earth self-assembly β-nucleating agents.

[0041] Figure 7 It is a compressive strength curve of foam materials with the same foaming ratio under different compressive strain conditions.

[0042] Figure 8 It is the crystallization behavior of β-nucleating agent TMB-5, NU-100 and rare earth self-assembly β-nucleating agent WBG-Ⅱ in LCBPP in Example 4, Comparative Example 7 and Comparative Example 8 respectively. DETAILED DESCRIPTION

[0043] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0044] Example 1

[0045] This embodiment provides a method for preparing a long-chain branched polypropylene microporous foam material based on a rare earth self-assembly β-nucleating agent, comprising the following steps:

[0046] Long chain branched polypropylene (LCBPP) particles were dried at 100°C for 2 hours, 100phr of LCBPP was mixed with 2phr of WBG-II (rare earth self-assembly β nucleating agent), and 1phr of antioxidant 1010 was added to prevent oxidation. The mixture was added to the torque rheometer, the temperature was set to 190°C, the speed was set to 90rpm, and the blending was performed for 10 minutes to obtain a modified LCBPP blend;

[0047] The obtained blend was placed in a molding device at a molding temperature of 290° C. for 3 minutes, and after cooling to room temperature, a 10 mm×10 mm×1 mm sample to be foamed was obtained;

[0048] The sample to be foamed is placed in an autoclave and filled with CO2 gas. The pressure is set to 10 MPa and the temperature is 145°C. After soaking for 1 hour, the pressure is quickly released to obtain a microporous foam material with uniform pore size.

[0049] The average diameter of the pores was 12.5 μm and the pore density was 3.6×10 9 Pieces / cm 3 The differential scanning calorimetry (DSC) test showed that the β-crystal crystallinity of the foamed sample was 5.63%, and the compressive strength was increased by about 118% compared with the LCBPP foam without adding the nucleating agent in Comparative Example 1.

[0050] Example 2

[0051] This embodiment provides a method for preparing a long-chain branched polypropylene microporous foam material based on a rare earth self-assembly β-nucleating agent, comprising the following steps:

[0052] 100 parts of LCBPP were blended with 3 phr of WBG-II, and 1 phr of antioxidant 1010 was added to prevent oxidation. The blending temperature was 190°C, the rotation speed was 90 rpm, and the blending time was 10 minutes.

[0053] The molding temperature is 290°C and the time is 3 minutes;

[0054] The same supercritical CO2 foaming conditions as in Example 1 were used to obtain a LCBPP foam material with a uniform pore structure.

[0055] The test results show that the cell density is increased to 4.1×10 9 Pieces / cm 3 The average cell diameter was reduced to 8.6 μm, and the β crystallinity of the foamed sample was increased to 5.75%. Mechanical tests showed that the foam compression strength was increased by 162% compared with Comparative Example 1.

[0056] Example 3

[0057] This embodiment provides a method for preparing a long-chain branched polypropylene microporous foam material based on a rare earth self-assembly β-nucleating agent, which is different from Embodiment 1 only in that:

[0058] The content of the rare earth self-assembly β-nucleating agent is 5 phr; and the molding temperature is 290°C.

[0059] The test results show that the cell density is 4.5×10 9 Pieces / cm 3 The average diameter of the pores was reduced to 6.8 μm, the β-crystal crystallinity of the sample to be foamed reached 6.45%, and the compressive strength was increased by about 87% compared with that of Comparative Example 1.

[0060] Example 4

[0061] This embodiment provides a method for preparing a long-chain branched polypropylene microporous foam material based on a rare earth self-assembly β-nucleating agent, which is different from Embodiment 1 only in that:

[0062] The content of the rare earth self-assembly β-nucleating agent is 2.5 phr.

[0063] The test results show that the cell density is 3.8×10 9 Pieces / cm 3 The average diameter of the pores is 7.9 μm, the β-crystal crystallinity of the sample to be foamed is 5.66%, and the compressive strength is increased by about 139% compared with Comparative Example 1.

[0064] Example 5

[0065] This embodiment provides a method for preparing a long-chain branched polypropylene microporous foam material based on a rare earth self-assembly β-nucleating agent, which is different from Embodiment 1 only in that:

[0066] The content of the rare earth self-assembly β-nucleating agent is 3.75 phr.

[0067] The test results show that the cell density is 4.3×10 9 Pieces / cm 3 The average diameter of the pores is 7.5 μm, the β-crystal crystallinity of the sample to be foamed is 5.83%, and the compressive strength is increased by about 178% compared with that of Comparative Example 1.

[0068] Comparative Example 1

[0069] This comparative example provides a method for preparing a long-chain branched polypropylene microporous foam material, which differs from Example 1 only in that:

[0070] The content of the rare earth self-assembly β-nucleating agent is 0 phr.

[0071] The test results show that the cell density is 2.3×10 7 Pieces / cm 3The average diameter of the pores is 142.5 μm, the β-crystal crystallinity of the sample to be foamed is 0%, and the compressive strength is increased by about 0%.

[0072] Comparative Example 2

[0073] This comparative example provides a method for preparing a long-chain branched polypropylene microporous foam material, which differs from Example 1 only in that:

[0074] The content of the rare earth self-assembly β-nucleating agent is 6.5 phr.

[0075] The test results show that the cell density is 5.1×10 9 Pieces / cm 3 The average diameter of the pores is 6.2 μm, the β-crystal crystallinity of the sample to be foamed is 7.1%, and the compressive strength is increased by about 69% compared with that of Comparative Example 1.

[0076] Comparative Example 3

[0077] This comparative example provides a method for preparing a long-chain branched polypropylene microporous foam material, which differs from Example 4 only in that:

[0078] The melt blending temperature was 250°C and the molding temperature was 290°C.

[0079] The test results show that the cell density is 1.2×10 7 Pieces / cm 3 The average cell diameter is 252.6 μm, the β crystallinity of the foamed sample is 1.35%, and the compression strength is 12% lower than that of comparative example 1. If the melt blending temperature is too high, the polypropylene matrix will be degraded, resulting in poor foaming performance.

[0080] Comparative Example 4

[0081] This comparative example provides a method for preparing a long-chain branched polypropylene microporous foam material, which differs from Example 4 only in that:

[0082] The foaming pressure is 20MPa.

[0083] The test results show that the cell density is 3.2×10 7 Pieces / cm 3 The average cell diameter is 189.5 μm, the β crystal crystallinity of the foamed sample is 0.78%, and the compression strength is increased by about 66% compared with that of comparative example 1. Since the pressure exceeds the range of the present invention, the third crystal type γ crystal is easily generated to compete, so the β crystal crystallinity value is relatively small.

[0084] Comparative Example 5

[0085] This comparative example provides a method for preparing a long-chain branched polypropylene microporous foam material based on a rare earth self-assembly β-nucleating agent, which is different from Example 4 only in that:

[0086] The content of the rare earth self-assembly β-nucleating agent is 0.25 phr.

[0087] The test results show that the cell density is 1.2×10 8 Pieces / cm 3 The average cell diameter is 59.7 μm, the β crystallinity of the foamed sample is 6.32%, and the compression strength is increased by about 65% compared with Comparative Example 1. The content of the nucleating agent in this comparative example is small, and too little nucleating agent does not completely refine the cells.

[0088] Comparative Example 6

[0089] This comparative example provides a method for preparing a long-chain branched polypropylene microporous foam material based on a rare earth self-assembly β-nucleating agent, which is different from Example 4 only in that:

[0090] The content of the rare earth self-assembly β-nucleating agent is 1.25 phr.

[0091] The test results show that the cell density is 3.9×10 8 Pieces / cm 3 The average diameter of the pores is 28.2 μm, the β-crystal crystallinity of the sample to be foamed is 5.54%, and the compressive strength is increased by about 92% compared with that of Comparative Example 1.

[0092] Comparative Example 7

[0093] This comparative example provides a method for preparing a long-chain branched polypropylene microporous foam material based on a β-nucleating agent, which differs from Example 4 only in that:

[0094] TMB-5 (aryl dicarboxamide β-nucleating agent) β-nucleating agent was used, and the content was fixed at 2.5phr. TMB-5 was not completely melted at the compression molding temperature of 290°C, but self-assembled into point-shaped, needle-shaped and fiber-shaped structures through the molecular rearrangement process guided by hydrogen bonds. When the temperature was lowered to 220°C, the molten parts at the ends of these fiber-shaped structures further developed into dendrites.

[0095] The test results show that the cell density is 3.2×10 9 Pieces / cm 3 The average diameter of the pores is 10.5 μm, the β-crystal crystallinity of the sample to be foamed is 4.33%, and the compressive strength is increased by about 98% compared with that of Comparative Example 1.

[0096] Comparative Example 8

[0097] This comparative example provides a method for preparing a long-chain branched polypropylene microporous foam material based on a β-nucleating agent, which differs from Example 4 only in that:

[0098] NU-100 (aromatic amide β-nucleating agent) β-nucleating agent was used, and the content was fixed at 2.5 phr. No NU-100 presence or self-assembly behavior was observed at compression molding temperatures of 290°C and 220°C.

[0099] The test results show that the cell density is 2.6×10 9 Pieces / cm 3 The average diameter of the pores is 15.1 μm, the β-crystal crystallinity of the sample to be foamed is 3.42%, and the compressive strength is increased by about 74% compared with that of Comparative Example 1.

[0100] The amounts of some raw materials used in the above embodiments and comparative examples and the performance test results of the long-chain branched polypropylene microporous foam materials are shown in Table 1.

[0101] Table 1

[0102]

[0103]

[0104] Experimental results and analysis

[0105] Figure 1 This is a diagram of the formation mechanism and foaming mechanism of the rare earth self-assembled β nucleating agent. The complex physical structure of the self-assembled and the induced composite pores work together to significantly improve the compressive strength of the polymer foam. Compared with the α-crystal, the β-crystal PP has a unique crystal structure. Its loose molecular chain arrangement and lattice defects make its melting point slightly lower, so it can be processed at a lower temperature, reducing equipment energy consumption and improving the thermal stability of the material.

[0106] The above examples and comparative examples were subjected to rheological tests. Figure 2The results of rheological tests on the storage modulus of LCBPP melt by rare earth self-assembled β-nucleating agents. The rheological property test shows that with the increase of WBG-Ⅱ content, the G′ dependence at low angular frequency increases, indicating the improvement of the storage modulus of the molecular chain. This may be related to the self-assembly behavior of the nucleating agent at high temperature. The self-assembled structure forms a more complex network in the polymer matrix, increasing the interaction between molecular chains and the macroscopic strength of the polymer. When the nucleating agent content exceeds 1.25phr, this effect reaches saturation, which means that further increasing the nucleating agent concentration does not lead to greater changes. In addition, the loss tangent (tanδ) value decreases with the increase of the nucleating agent self-assembly concentration, indicating that the elastic response of the melt is enhanced and the viscous loss is reduced. With the increase of the nucleating agent concentration, the increase of the complex viscosity (η*) reflects the increased difficulty of melt deformation, which directly reflects the enhancement of the strength of the polymer melt by the self-assembled structure. These results indicate the key role of the self-assembled structure of rare earth self-assembled nucleating agents in enhancing the rheological properties of LCBPP, especially the microstructure formed at high temperature is crucial to improving the macroscopic properties of the polymer melt.

[0107] Figure 3 The following are the DSC and XRD diagrams of foam materials containing different contents of nucleating agents. Using differential scanning calorimetry (DSC, Figure b) and X-ray diffraction (XRD, Figure a). According to the DSC results, the melting temperature of the β crystal of the foam material with a content of 2.5phr is 142°C, which is 18°C ​​lower than that of the sample without nucleating agent; XRD analysis shows that the crystallinity ratio of β crystal is increased by more than 15%. This result confirms that the rare earth self-assembled β nucleating agent significantly improves the crystallinity and thermal stability of the material.

[0108] Figure 4 This is a mechanical properties test chart of tensile strength and impact strength of different contents of nucleating agents. The self-assembly of rare earth self-assembly β-nucleating agents significantly improves the mechanical properties of the material. As the content of rare earth self-assembly β-nucleating agents increases, the impact strength of the polymer spline increases. The impact strength of the pure spline (0phr nucleating agent) is 3.13kJ / m 2 The impact strength of the strip containing 0.25phr nucleating agent becomes higher, which may be due to the relatively high crystallinity of β crystals after high-temperature self-assembly, which enhances the toughness of the LCBPP matrix. When the nucleating agent content is higher than 2phr, the impact strength increases sharply, and the impact strength reaches 5.36kJ / m when the nucleating agent content is 5phr. 2 , which is 75% higher than that of pure polypropylene samples. This is due to the synergistic reinforcement effect of the uniform and complex crystal network formed by the self-assembly of the nucleating agent on the LCBPP matrix. In addition, the tensile strength of the spline gradually decreases with the increase of the nucleating agent content, but the reduction does not exceed 10%, which indicates that the rigidity of the polymer is slightly reduced, and the rigid-toughness balance is basically achieved.

[0109] Figure 5 The polarizing microscope (left) and scanning electron microscope (right) images of different molding temperatures under the condition of 2.5phr of rare earth self-assembling β nucleating agent. There is a difference in the processing temperature between the self-assembling nucleating agent LCBPP and the non-self-assembling nucleating agent LCBPP. The setting of the molding processing temperature (such as 280-290℃) must ensure that the self-assembling nucleating agent melts first and forms a dendritic self-assembling structure during the cooling process. If the temperature is too low (such as 200℃), the self-assembling nucleating agent cannot melt, resulting in no self-assembling structure. Figure 5 It is shown that the rare earth self-assembly β-nucleating agent WBG-II of the present invention can form a stable dendritic physical network structure, such as dendritic and flower-like, in the LCBPP matrix material (sample to be foamed) through its self-assembly structure, which can be used as a nucleation site, showing the effect of pore refinement, significantly reducing the pore size, increasing the pore density, and finally increasing the mechanical properties.

[0110] Figure 6 The following is a statistical chart showing the effect of different contents of rare earth self-assembly β-nucleating agents on the expansion ratio, cell size and cell density of foam materials. Figure 6 As shown in the figure, with the increase of the content of rare earth self-assembled β-nucleating agent, the cell size (red line) of the foam sample decreases significantly, and the cell density (blue line) increases. This is because the rare earth self-assembled β-nucleating agent inhibits the excessive growth of the cells through the physical network structure and increases the nucleation density of the cells. When the nucleating agent content reaches 5phr, the cell size reaches the minimum and the density reaches the maximum, which indicates that the cell structure is the most fine and uniform at this time.

[0111] Figure 7 It is the compression strength curve of the foam material with the same foaming ratio (15 times) under different compression strain conditions. According to the compression performance test results of the foam material, as the content of the rare earth self-assembled β-nucleating agent increases, the compression strength of the foam material first increases and then decreases. When the nucleating agent content is moderate, the small bubble structure provides more opportunities for contact and friction between the bubble walls, thereby improving the compression strength. However, when the nucleating agent content exceeds 5phr, the excessive refinement of the bubbles leads to an increase in the rupture and merging of the bubble walls, and the compression strength begins to decrease. This shows that the content of the rare earth self-assembled β-nucleating agent has an important influence on the compression performance of the foam material, and the content of the nucleating agent within the scope of the present invention helps to improve the mechanical properties of the foam.

[0112] Figure 8The crystallization behaviors of β-nucleating agents TMB-5, NU-100 and rare earth self-assembling β-nucleating agent WBG-Ⅱ in LCBPP in Example 4, Comparative Example 7 and Comparative Example 8 respectively. The results show that TMB-5 is not completely melted at 290°C, and self-assembles into point-like, needle-like and fibrous structures through the molecular rearrangement process guided by hydrogen bonds. When the temperature is lowered to 220°C, the completely melted part further develops into a dendrite. The presence or self-assembly behavior of NU-100 was not observed at 290°C and 220°C. WBG-Ⅱ completely melts at 290°C, and begins to precipitate and self-assemble into a dendrite-like or even "flower"-like complex physical structure when the temperature is lowered to 220°C.

Claims

1. A method for preparing a long-chain branched polypropylene microporous foam material based on a rare earth self-assembly β-nucleating agent, wherein: The following steps are involved: Step 1: blending long-chain branched polypropylene with a rare earth self-assembly β-nucleating agent to obtain a blend; Step 2: Compression molding the blend to obtain a sample to be foamed; Step 3: The sample to be foamed is foamed by a foaming agent to obtain the long-chain branched polypropylene microporous foam material; Wherein, based on 100phr of long-chain branched polypropylene, the added amount of the rare earth self-assembly β-nucleating agent is 2-5phr.

2. The method for preparing a long-chain branched polypropylene microporous foam material according to claim 1, wherein: Calculated based on 100 phr of long-chain branched polypropylene, the added amount of the rare earth self-assembly β-nucleating agent is 2-4 phr.

3. The method for preparing a long-chain branched polypropylene microporous foam material according to claim 1, wherein: The rare earth self-assembly β nucleating agent is selected from WBG-II; And / or, the long-chain branched polypropylene is selected from one or a combination of two or more of HMS-WB140, E02ES, and T30S, preferably HMS-WB140.

4. The method for preparing a long-chain branched polypropylene microporous foam material according to any one of claims 1 to 3, wherein the step 1 further comprises: After long-chain branched polypropylene and a rare earth self-assembly β-nucleating agent are blended, an antioxidant is added to obtain a blend; Preferably, based on 100 phr of long-chain branched polypropylene, the added amount of the antioxidant is 0-5 phr, more preferably 0.5-2 phr.

5. The method for preparing a long-chain branched polypropylene microporous foam material according to claim 1, wherein: In step 2, the β-crystal crystallinity of the sample to be foamed is 1%-10%; And / or, in step three, the sample to be foamed is foamed by supercritical CO2 and then pressure is maintained to obtain the long-chain branched polypropylene microporous foam material.

6. The method for preparing a long-chain branched polypropylene microporous foam material according to claim 5, wherein: The pressure of the foaming treatment is 5-17 MPa, preferably 8-15 MPa; And / or, the temperature of the foaming treatment is 140-170°C, preferably 140-150°C; And / or, the pressure holding time is 0.1-5h, preferably 1-2h.

7. The method for preparing a long-chain branched polypropylene microporous foam material according to claim 1, wherein: The blending temperature is 150-200°C, preferably 170-190°C; And / or, the blending speed is 50-100 rpm, preferably 60-90 rpm; And / or, the blending time is 6-12 minutes, preferably 8-12 minutes.

8. The method for preparing a long-chain branched polypropylene microporous foam material according to claim 1, wherein: The temperature of the compression molding is 250-300°C, preferably 280-300°C; And / or, the compression molding time is 2-5 minutes.

9. A long-chain branched polypropylene microporous foam material obtained by the method for preparing a long-chain branched polypropylene microporous foam material based on a rare earth self-assembly β-nucleating agent as described in any one of claims 1 to 8.

10. The long-chain branched polypropylene microporous foam material according to claim 9, wherein: The average diameter of the pores of the long-chain branched polypropylene microporous foam material is 5-13 μm; And / or, the cell density of the long-chain branched polypropylene microporous foam material is 2×10 8 -6×10 9 Pieces / cm 3 .

Citation Information

Patent Citations

  • Extruded foamed polypropylene beads and their preparation method

    CN102295807A

  • Extrusion foaming polypropylene particles with lower thermal molding temperature and preparation method thereof

    CN102391570A

  • Method for improving nucleation efficiency when preparing beta crystalline long-chain branching polypropylene through beta nucleating agent

    CN109810411A

  • Polypropylene-based in-situ microfiber foaming material with beta nucleating agent selective distribution and preparation method thereof

    CN109836702A

  • Toughness improving method, preparation method and application of thermal expansion microsphere foaming polypropylene material

    CN116589788A